Impact of Agricultural Technology on Rice Farmers Welfare in Bojongjaya Village, Pusakajaya District, Subang Regency - Cicih Roisah; Yati Haryati; Dewi Fatmasari (Cirebon International Journal of Economics and Business, 2023)
Rice farmers in Pusakajaya sub-district primarily rely on traditional agricultural systems, neglecting the potential of Good Agricultural Practices (GAP) technology. This study investigates how GAP adoption impacts rice farmers' well-being in this context. Methodology:The study employs a qualitative approach, chosen for its effectiveness in exploring and describing objects and phenomena in detail. This allows for a more direct representation of the relationship between researchers and respondents, facilitating deeper understanding of the lived experiences and perspectives of rice farmers. Data collection involved interviews with farmers and other stakeholders, providing rich insights into the perceptions and realities of GAP adoption in the context of Pusakajaya. Findings reveal that GAP technology holds significant promise for wider adoption due to its demonstrably positive effects on crop yields and farmer income. Increased yields and improved quality translate to enhanced market value and greater profits, ultimately contributing to improved farmer well-being.